Wetting characteristic and flow behavior of silicate binder at various sand particle-particle interfaces: Fine or coarse, circular or angular particles - Jinpeng Li; Huarui Zhang; Zhanxin Li; Ming Du; Jiulong Chen; Yesheng Xiong; Hu Zhang; Ying Cheng (Journal of Materials Research and Technology, 2023)
This study presents an innovative investigation into the wetting characteristic and flow behavior of sand particles, which have different shapes, sizes, and textures, when they bonded with silicate binder. The results revealed that the apparent contact angles of fine and angular particles with the binder are higher than those of coarse and circular particles. In addition, after modifying the four systems with anionic surfactants, the equilibrium contact angles decreased by 42.8%, 26.7%, 26.5%, and 7%. These findings suggest that coarse and circular particles demonstrate stronger wetting properties with the binder compared to fine and angled particles. Additionally, the cohesion and internal friction angle of the wet sand mixture can be measured through the ring shear test. Moreover, the unconfined yield strength and main consolidation stress can be calculated using the Mohr Coulomb model to obtain the yield locus and quantify the flowability of the wet sand mixture. The yield trajectory of sand mixtures at specific consolidation stresses suggests that the most important factor affecting the flowability of wet sand particles is particle size distribution. Wet mixtures of coarse and circular particles exhibit lower cohesive forces, indicating higher fluidity.